Human Acts in Ḍirār’s Theology: Continuous Divine Creation and Human Responsibility - Azad Raouf Qazaz (Rumah Moderasi Beragama of UIN Siber Syekh Nurjati Cirebon, 2026)
Purpose ̶ This article examines Ḍirār b. ʿAmr’s (d. c. 193/809) doctrine of khalq afʿāl al-insān (the createdness of human acts) and its relationship to divine omnipotence, human moral responsibility, and tawḥīd. Although Ḍirār is recognized as one of the formative theologians of early kalām, his theology has largely been reconstructed from later heresiographical sources because his own writings were long considered lost. Design/methods/approach ̶ Drawing on the recently rediscovered Kitāb al-Taḥrīsh (The Book of Provoking), together with reports preserved by later theologians, this study reconstructs his theology through a comparative analysis of the surviving primary sources and their later reception. Findings ̶ It examines al-istiṭāʿa (ability), kasb (acquisition), causality, perception (idrāk), and the createdness of the Qurʾān as interconnected elements of a unified theological system. It argues that these doctrines form an integrated theological architecture grounded in God’s continuous creative activity. Conclusion ̶ Accordingly, God alone is the Creator of all acts, while human beings acquire moral responsibility through kasb. Research Implication ̶ By reconstructing Ḍirār’s theology in this way, the article offers a new framework for understanding his thought and contributes to a more nuanced understanding of the formative development of early Islamic kalām.